2013
DOI: 10.1371/journal.pone.0064586
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid-and Retinol-Binding Protein, Mj-FAR-1 Induces Tomato Host Susceptibility to Root-Knot Nematodes

Abstract: Plant-parasitic nematodes produce at least one structurally unique class of small helix-rich retinol- and fatty-acid-binding proteins that have no counterparts in their plant hosts. Herein we describe a protein of the plant-parasitic root-knot nematode Meloidogyne javanica, which is a member of the nematode-specific fatty-acid- and retinol-binding (Mj-FAR-1) family of proteins. The mj-far-1 mRNA was detected through M. javanica pre-parasitic J2s, migratory and sedentary parasitic stages by quantitative reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
109
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(117 citation statements)
references
References 92 publications
4
109
1
3
Order By: Relevance
“…However, in contrast with this work, G. pallida and M. javanica FAR-1 proteins have been shown to be highly expressed in the migratory and parasitic J2 with transcription in the nematode surface and also within the adult female body, using immunolocalization studies with the same antiserum (Prior et al 2001;Iberkleid et al 2013). Although M. hispanica far-1 formed a well supported clade (100 %) with M. incognita it showed only 67 % bootstrap with M. javanica which could We also showed in this paper that the localization of Mhi-far-1 is similar to M. incognita FAR protein but differs in M. hispanica in comparison with M. javanica (Bellafiore et al 2008;Iberkleid et al 2013).…”
Section: Discussioncontrasting
confidence: 79%
See 4 more Smart Citations
“…However, in contrast with this work, G. pallida and M. javanica FAR-1 proteins have been shown to be highly expressed in the migratory and parasitic J2 with transcription in the nematode surface and also within the adult female body, using immunolocalization studies with the same antiserum (Prior et al 2001;Iberkleid et al 2013). Although M. hispanica far-1 formed a well supported clade (100 %) with M. incognita it showed only 67 % bootstrap with M. javanica which could We also showed in this paper that the localization of Mhi-far-1 is similar to M. incognita FAR protein but differs in M. hispanica in comparison with M. javanica (Bellafiore et al 2008;Iberkleid et al 2013).…”
Section: Discussioncontrasting
confidence: 79%
“…However, FAR proteins clearly distinguished and grouped different nematode species according to their trophic group and nematode parasitism strategy. The highest predicted amino acid identity of Mj-FAR-1 was found amongst M. incognita, M. arenaria and M. hapla and the lowest observed between M. javanica and M. chitwoodi (Iberkleid et al 2013). Although, there is a strong conservation for this group of proteins, M. hapla in this study showed to be the most divergent when compared with M. hispanica, which might account for a particular mode of parasitism adaptation and/or reproduction.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations